Discrimination without taste: how discrimination can spillover and persist - Ramachandran, Rajesh; Rauh, Christopher (SERIEs, 2018)
We introduce coordination failures driven by beliefs regarding the presence of taste discriminators as a channel of discrimination in productive activities requiring the input of multiple agents. We show that discrimination can persist under perfectly observable ability, when taste for discrimination has died out, and under absence of discriminatory social norms. Empirically we analyze the market for self-employment-an activity commonly requiring inputs from multiple agents. Consistent with the theoretical predictions, beliefs about discrimination are a significant correlate of self-employment rates, as well as the cost and success of establishing productive relations for blacks in the US.
Keywords: Aufsatz in Zeitschrift